2017
DOI: 10.1002/ijc.30700
|View full text |Cite
|
Sign up to set email alerts
|

Gastric microbiota features associated with cancer risk factors and clinical outcomes: A pilot study in gastric cardia cancer patients from Shanxi, China

Abstract: Little is known about the link between gastric microbiota and the epidemiology of gastric cancer. In order to determine the epidemiologic and clinical relevance of gastric microbiota, we used 16S ribosomal RNA gene sequencing analysis to characterize the composition and structure of the gastric microbial community of 80 paired samples (non-malignant and matched tumor tissues) from gastric cardia adenocarcinoma (GCA) patients in Shanxi, China. We also used PICRUSt to predict microbial functional profiles. Compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 29 publications
(53 reference statements)
2
32
1
1
Order By: Relevance
“…The relative abundance of Helicobacter ranked second in our GCA tumor tissues after the relative abundance of Prevotella , and this is in contrast to the previous study . We did not find any significant difference in α diversity or the relative abundance of specific taxa by GCA stage, and this is in accordance with a previous study . However, we observed a nonsignificant decrease in Helicobacter and an increase in Prevotella with a more advanced GCA tumor stage.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…The relative abundance of Helicobacter ranked second in our GCA tumor tissues after the relative abundance of Prevotella , and this is in contrast to the previous study . We did not find any significant difference in α diversity or the relative abundance of specific taxa by GCA stage, and this is in accordance with a previous study . However, we observed a nonsignificant decrease in Helicobacter and an increase in Prevotella with a more advanced GCA tumor stage.…”
Section: Discussionsupporting
confidence: 81%
“…28 We did not find any significant difference in α diversity or the relative abundance of specific taxa by GCA stage, and this is in accordance with a previous study. 29 However, we observed a nonsignificant decrease in Helicobacter and an increase in Prevotella with a more advanced GCA tumor stage.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…Other smaller studies detailing the GC microbiome also confirmed a reduction in H. pylori abundance in GC tissue alongside a concomitant increase in other bacterial species . The Castano‐Rodriguez study did not show the reduction in α‐diversity seen in other studies but showed that H. pylori ‐positive patients had higher species richness and serological status was a significant on diversity and composition suggesting the composition of the gastric microbiome is shaped by the immune response .…”
Section: Gastric Microbiomementioning
confidence: 74%
“…However, few studies focus on the microbial community in the gastric cardia. Recently, it had been reported that the gastric microflora was a major risk factor in GCC patients . Bacterial infection can cause inflammation, leading to the production of reactive oxygen species (ROS) and subsequent DNA oxidative damage and genomic instability thus posing a risk for the development of cancer .…”
Section: Introductionmentioning
confidence: 99%